Distal Deletion of Chromosome 11q Encompassing Jacobsen Syndrome without Platelet Abnormality. (January 2014) - Sheth, Frenny J.; Datar, Chaitanya; Andrieux, Joris; Pandit, Anand; Nayak, Darshana; Rahman, Mizanur; Sheth, Jayesh J.
Terminal 11q deletion, known as Jacobsen syndrome (JBS), is a rare genetic disorder associated with numerous dysmorphic features. We studied two cases with multiple congenital anomalies that were cytogenetically detected with deletions on 11q encompassing JBS region: 46, XX, der(11) del(11)(q24). Array comparative genomic hybridization (aCGH) analysis confirmed partial deletion of 11.8–11.9 Mb at 11q24.1q25 (case 1) and 13.9–14 Mb deletion at 11q23.3q25 together with 7.3–7.6 Mb duplication at 12q24.32q24.33 (case 2). Dysmorphism because of the partial duplication of 12q was not overtly decipherable over the Jacobsen phenotype except for a triangular facial profile. Aberrant chromosome 11 was inherited from phenotypically normal father, carrier of balanced translocation 46, XY, t(11;12)(q23.3; q24.32). In the present study, both cases had phenotypes that were milder than the ones described in literature despite having large deletion size. Most prominent features in classical JBS is thrombocytopenia, which was absent in both these cases. Therefore, detailed functional analysis of terminal 11q region is warranted to elucidate etiology of JBS and their clinical presentation.